Playing Activities Improve Manipulative Skills: a Literature Review - Palupi Ardanari; Edy Mintarto; Abdul Rahman Syam Tuasikal; Suroto Suroto (Universitas STRADA Indonesia, 2020)
Playing activities provide positive stimulation for manipulative movement skills of children aged 6-12 years. Playing activities, including physical activities that have the opportunity to reduce the risk of obesity in children aged 6-12 years. Playing activity interventions in obese children are recommended on basic motion skills and motion coordination. The purpose of the review in this journal is to show the contribution of playing activities to children's manipulative movement skills. The review method that used was a journal search system with keywords manipulative motion skills on Google. 12 national journals have been reviewed based on playing activity models, methods, samples, and research results. The conclusion of the review results showed that variations in playing activities undertaken by children positively contribute to the manipulative movement skills of children in living their daily lives.